Examining the Dimensions of Corporate Taxpayer Compliance (Phenomenological Studies) - Aripratiwi, Ratna Anggraini; Khoirul Umam Hasbiy (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2023)
This study aims to explore the deep meaning of the phenomena of taxpayer compliance in Indonesia through the phenomenology method. Disclosing the attitude of tax compliance is based on several reasons, including the low level of state tax revenue, the decline in public trust due to tax scandals, and the low level of awareness of taxpayers in Indonesia. The results show that each individual has a perspective based on experience. Tax compliance is interpreted as an attitude of compulsion, sincerity, and fear of the rules that the government has made. This research is expected to provide input for the government in developing tax regulations so that they are not only oriented towards pragmatic and material decisions but also towards non-material values.